2021
DOI: 10.1097/jsm.0000000000000940
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin-T Release After Sport and Differences by Age, Sex, Training Type, Volume, and Intensity: A Critical Review

Abstract: Background:Postexercise release of cardiac troponin (cTn) is a well-known phenomenon, although the influence of various confounders remains unclear. The aim of this critical review was to analyze the postexercise release of cTn according to age, sex, different types of sport, exercise intensity and duration, and training level.Data Sources:A literature search was performed within the National Library of Medicine using the following keywords: cTn, peak, release, and exercise. The search was further refined by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 87 publications
(992 reference statements)
0
5
0
1
Order By: Relevance
“…We did, however, observe a difference in Troponin T values between athletes and controls where three of the athletes and none of the controls exceeded the upper reference limit for Troponin T for our laboratory. Athletes were not detrained prior to investigation, hence this could be explained by post exercise rise in cardiac troponins which is a well-known and usually physiologic phenomenon 40 . Although being asymptomatic, this could alternatively be a sign of sub-clinical cardiac disease in these athletes.…”
Section: Discussionmentioning
confidence: 99%
“…We did, however, observe a difference in Troponin T values between athletes and controls where three of the athletes and none of the controls exceeded the upper reference limit for Troponin T for our laboratory. Athletes were not detrained prior to investigation, hence this could be explained by post exercise rise in cardiac troponins which is a well-known and usually physiologic phenomenon 40 . Although being asymptomatic, this could alternatively be a sign of sub-clinical cardiac disease in these athletes.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that prolonged strenuous exercise may lead to an elevation of cardiovascular biomarkers such as hs-cTnI and NT-proBNP [ 6 , 14 16 ]. Zebrowska et al demonstrated in participants of a 24-h ultramarathon that cTnI and NT-proBNP were significantly elevated directly and one day after the race [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the postexercise release of cTn rarely underlies a subclinical cardiac disease and can be considered a physiological phenomenon observed in athletes of all ages. Future studies are needed to establish the influence of confounders (such as age, sex, sport type, intensity and duration) and individualized ranges of normality of post-exercise cTn levels in athletes [ 61 ].…”
Section: Acute Effectsmentioning
confidence: 99%